Humor intervention in the nurse-patient interaction - Luis Manuel Mota Sousa; Cristina Maria Alves Marques-Vieira; Ana Vanessa Antunes; Maria de Fátima Graça Frade; Sandy Pedro Silva Severino; Olga Sousa Valentim
ABSTRACT Objective: To describe the factors influencing the use of humor in nursing care, its applicability and benefits. Method: A scoping review was performed using the Arksey and O'Mally methodology. A search for articles published between 2008 and 2018 was performed using the platforms EBSCO Host, Virtual Health Library and Google Scholar. Results: From the initial 465 articles found, 17 were included for final revision. Data allowed to retrieve information on humor definition; its applicability as a nursing intervention; humor as a tool to improve nurse-patient communication and relationship; influence factors; type of humor interventions; humor benefits in health care context and; limitations and precautions of humor intervention. Conclusion: The use of humor promotes both communication and human interaction; it promotes well-being; helps deal/cope with difficult and unpleasant situations, reduces tension, discomfort and stress; and strengthens the immune system. This intervention should be used with caution.